MENTAL ACCOUNTING DAN DAMPAKNYA TERHADAP KINERJA PERUSAHAAN MELALUI PENEMPATAN MODAL KERJA PADA USAHA KECIL DAN MENENGAH DI PULAU LOMBOK - Hidayati, Siti Aisyah (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
This study aims at analyzing: 1) the effect of mental accounting on placement of funds for working capital in small- and middle-scale business, 2) the effect of placement of funds for working capital on company performance in small-and middle-scale business, and 3) the effect of mental accounting on company performance through placement of funds for working capital in small- and middle-scale business. The population of this study was all the small- and middle-scale businesses in Lombok Island. Samples were collected by using judgment sampling of non probability sampling. The samples taken were the small- and middle-scale businesses of pottery industry which have exported their goods. The respondents were the managers and owners of small- and middle-scale businesses. The method of data analysis employed in this study was Generalized Structured Component Analysis. The finding of this study showed that mental accounting is rational by nature and have significant effects on company performance through placement of funds for working capital in small-and middle-scale business.This phenomenon is grounded from the fact that most managers and owners of those small- and middle-scale businesses are men who are on their productive age, and have more than 10 years of experience. The placement of funds for working capital is shown by the efficiency of cash, receivable and inventory management which in turn improve the company performance. Keywords: mental accounting, working capital, company performance